Fellowship and Practice Trends in Neuroradiology Training Programs in the United States - Friedman, David P. (AJNR Am J Neuroradiol, 2001)
BACKGROUND AND PURPOSE: Neuroradiology has become an increasingly diverse and subspecialized discipline. We evaluated the current status and trends affecting fellowship programs and the practice of clinical neuroradiology at academic medical centers, with emphasis on invasive procedures. METHODS: All 85 program directors at Accreditation Council for Graduate Medical Education–approved fellowships in neuroradiology were sent a detailed questionnaire pertaining to various demographic aspects of their program and the performance of certain radiologic examinations of the brain and spine. RESULTS: Sixty-seven programs (79%) responded. As many as 50% of programs are 1 year in length. Twenty-five percent of 2-year fellows leave their program after 1 year of training. During the past 5 years, 36% of programs have decreased in size and 73% reported a decline in the number of applicants. The majority (55%) of programs have had applicants renege on their commitment to begin a fellowship. Twenty percent of 2-year programs do not offer training in endovascular interventional procedures. Neurosurgeons perform endovascular interventional procedures at 18% of centers. There is an 18-fold variation in the volume of neuroangiographic procedures performed each year and a 150-fold variation in the volume of myelographic procedures performed. In 29% of programs, neuroradiologists are nonparticipants in nonvascular interventional spinal procedures; in 40%, they share these procedures with musculoskeletal radiologists/nonradiologists. CONCLUSION: Interest in fellowship programs in neuroradiology is declining. An applicant's commitment to either begin a fellowship or complete 2 years of training cannot be regarded with assurance, and there is a lack of uniformity in many areas of the training experience, particularly in invasive diagnostic and therapeutic procedures.